Veiksmažodžio beasmenių formų ir darinių semantinės-funkcinės ypatybės lietuvių ir anglų kalbose - Anglickas, Vaidotas Vaclovas (Kalbotyra, 1994)
Non-finite forms of the verb (verbids) and verbal derivatives (abstract nouns and adjectives) of the English and Lithuanian languages are compared in the paper. The analysis shows that there exists strongly pronounced analogy in their meaning and functions. It manifests itself in combining the categorial meanings of two different parts of speech in one form and their ability to denote whole extralinguistic situations by means of expressing secondary or potential predication and forming nominal syntacical complexes directly related to clauses with predication, expressed in its full, complete, genuine form by finite forms of the verb. The categorial processual meaning of the verb, dominating in the meaning of verbids and verbal derivatives mainly determines their combinability, whereas their secondary part-of-the speech meaning (nounal or adjectival) chiefly determines their functions in the sentence. Though in many cases the semantic equivalence of verbids and derivatives is observed, there is a general tendency of their mutual differentiation and complementation in usage by different type of processual presentation - static, dynamic or semi-dynamic.The structural characteristics and differences of languages most clearly manifest themselves through the system of verbal forms and derivatives. The usage of forms and derivatives, presenting process as an abstract substance, and nominalization processes based on them are restricted in the Lithuanian language, whereas there are practically no essential restrictions in this respect in the English language. The grammatical and lexical characteristics of action, denoted by verbids and derivatives, in Lithuanian are expressed in a more full, explicit, concrete and detailed way then in English and mainly morphological means of expression are used for that. In the English language verbids and derivatives are more abstract, implicit in this respect, chiefly syntactic means of expression being used. The homonymy is widespread among verbids and verbal derivatives in the English language and their meaning is more dependant on the context than in the Lithuanian language.